Can cooperatives commercialize farming in Malawi? - Davis, Kristin E.; Kazembe, Cynthia; Benson, Todd; De Weerdt, Joachim; Duchoslav, Jan (International Food Policy Research Institute, 2023)
Smallholder farmers constitute the largest group of economic actors in Malawi and there is increasing recognition that the small scale at which they operate does not offer for most a pathway out of poverty, let alone to prosperity. Increasingly the idea is gaining traction that by joining forces through primary agricultural cooperatives, smallholder farmers across Malawi can reap many of the benefits that larger farmers on commercial estates have been able to realize, such as  negotiating better price for agricultural inputs through bulk purchases;  negotiating better prices for agricultural outputs through aggregation and storage;  adding value to raw agricultural products;  accessing professional equipment, such as tractors or irrigation;  hiring professional services, such as a farm or business manager; or  pooling contiguous pieces of land for more efficient farming. In this brief we summarize the findings of a detailed report (Davis et al., 2022) on research conducted to assess the current status of cooperatives in the country and what project implementers and policymakers can do to enable cooperatives to contribute to increased commercialization and professionalization of smallholder farming in Malawi.